Algoritm for diagnostics of appendicitis in childhood and SIRS - Y. Dimcheva; Kr. Kalinova; K. Georgiev (Trakia Journal of Sciences)
The specific purpose of this study was to describe and characterize the systemic inflammatory response to appendicitis in childhood. The clinical symptoms of SIRS are present in a large proportion of patients . A study of high-risk patients showed that over a given period of time, 44-68% of the patients met the criteria for this condition, while at the same time they had proven infection up to 50%.The incidence of SIRS is even higher in the post-operative period and in trauma regardless of the presence or absence of infection. On the other hand, between 10% and 43% of patients with proven sepsis do not meet the SIRS criteria.The inclusion of a number of biological markers (C-reactive protein, procalcitonin, cytokines) aims to help differentiate SIRS with infectious and noninfectious etiology. Sixty six patients were studied, divided into four groups from onset of symptoms to diagnosis. The primary outcome measure was to determine the systemic inflammatory response to appendicitis according to the established groups of time intervals. The secondary outcome measure was the analysis of C-reactive protein for the same purpose. The variables of the systemic inflammatory response, according to diagnostic intervals, showed non-significant differences in white blood cell count. The temperature rose constantly after 48 h, reaching its peak after 72 h (p = 0.001), and the respiratory rate rose after 72 h (p < 0.0001). After 73 h, most patients had three or four systemic inflammatory response criteria (p < 0.0001). C-reactive protein levels rose progressively, showing higher levels after 48 h (p = 0.005). The inflammatory response to appendicitis is progressive, being more marked along the timeline from onset of symptoms to diagnosis. Key words: appendicitis, diagnostic SIRS, children, algoritm.